Urgency of Indonesian Waters Area Protection from Illegal Unreported Unregulated Fishing - F.P, Ramadhan Marco; L.N.A, Mutiara Firsty; A., Sutan Syahnendra (Universitas Sebelas Maret, 2020)
Indonesia as the largest archipelagic country has considerable potential with vast areas of water that can be utilized, but it must be accompanied by strict supervision because of many illegal practices such as IUU Fishing. This problem becomes important to deal with because Indonesia's maritime potential cannot be maximized as long as IUU Fishing practices remain. The author(s) formulated a problem in the form of